PROBLEMATIKA SEPUTAR HUKUM ISBAT NIKAH DALAM SISTEM HUKUM PERKAWINAN INDONESIA - Mardoni (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
Marriage certificate is the determination of a marriage. Juridically, isbat marriage is regulated in laws and regulations such as Law Number 1 of 1974 concerning Marriage, Law Number 7 of 1989 concerning Religious Courts, and Law Number 3 of 2006 and Law Number 50 of 2009 concerning Changes to the Law on Religious Courts. The regulation confirms that marriage certificates are permitted in marriages prior to Law Number 1 of 1974. In practice, marriage certificates submitted to the Religious Courts are carried out after the enactment of Law Number 1 of 1974. The application for marriage certificates is granted by the Religious Court in marriages held after the 1974 Marriage Law was based on the Compilation of Islamic Law (KHI), even though the legal position of KHI was not included in the statutory order. The essence of isbat marriage is stipulation. This means that the marriage that is isbat is still valid because the marriage that is isbat is administrative. The position of the marriage certificate is part of legal protection and legal certainty. The position of the KHI, which regulates in more detail regarding marriage certificates, has a regulatory function in the midst of a void in the material law of the religious courts. In addition, judges can determine whether an application for marriage registration is granted or rejected. Thus, it can be concluded that the essence of marriage confirmation is part of legal discretion.